OPTIMASI TUNGKU PELEBURAN LOGAM ALUMINIUM KAPASITAS 10 KG BERBAHAN BAKAR OLI BEKAS SKALA LABORATORIUM - Budi Istana; Abrar Ridwan; Ade Rilnanda (Sistem Informasi, 2017)
Metal melting furnace is a device used to fuse a metal. In the world of metal furnace industry is still dominated by liquid fuel in the form of diesel or solid fuel in the form of coal. In this research the source of fuel used is waste of used oil. Used oil is a waste that is promising when in the process of becoming fuel. The purpose of this study for the optimization clicking or enhance an aluminum melting furnace and get better efficiency in terms of the manufacturing process, design, raw materials, fuel consumption, time, procedures for use. This study was conducted using an experimental method to build the furnace and burner that will be used for smelting logam.isolator used is refractory cement (TNC 16) and Glass Wool. The capacity created in this study is 10 kg of aluminum. In designing the software use ANSYS 12.1 to simulate the state when in operation. The furnace was tested with variable weight of aluminum to be melted: 0.5 kg, 1 kg, 0.5kg. Later tempratur on the furnace in measuring on the inside, the outside, cover, and fuel consumption. From the results of tests and calculations get the amount of time required for the melt of 0.5 kg, 1 kg and 1.5 kg of solid aluminum is ± 29-34 minutes. The time required until the 660 oC temprature is ± 24 minutes. The pouring temperature of this test reaches 887 oC. Q losses are 19,48197 kw and the resulting heat is 128854,91 kj.